Databasing dragonflies: State of knowledge in the Neotropical region - Von Ellenrieder, Natalia (2009)
The Neotropical region extends from the lowlands of Mexico to central Argentina. The fauna from the highlands of N Mexico belongs to the Nearctic region, and that of temperate forests of SW Argentina and Chile to the Austral region (Morrone 2001). However, in order to simplify the analysis and to allow for comparison with previous studies (Paulson 2004; Kalkman et al. 2008), the entire area extending from all of Mexico to S South America will be here referred to as Neotropical region.